Existential Process in Harry Potter and the Chamber of Secret: A Systemic Functional Linguistic Study - Afrianto Afrianto; Anisa Inayati (TEKNOSASTIK, 2016)
Dealing with sense of experience people undergo, transitivity construes the process of the experiences. One of the processes in transitivity is discussed here, that is existential process. Qualitatively conducted, this research employs Hallidayan theoretical framework especially transitivity which covers six processes, they are material, mental, verbal, behavioural, relational and the last one is existential process.  This process construes existence of matters such as people, things, events, actions and moments which are called as existent. Discussing process, this research focuses on clause because transitivity analysis lies on clauses. Basically, clauses found are not all in form of clause but some of them are taken from clause complex which are then broken down into clauses. Further, there are twenty clauses found engaging existential processes and dummy subject (there). Those processes are auxiliary verb or to be (was and were). Thus far, the existential processes construe two types of existent, they are entity and event. Thirteen of twenty clauses carry out the existent of entity which covers people and things while the rest construe the existent of event which covers action and moment. Another point found is circumstance; there are ten circumstances which are categorized into three types, they are circumstance of place, circumstance of time, and circumstance of manner (comparison).